Young Generation and Hoax Danger in The Middle of The Community - Rosy Febriani Daud; Khairunnisa Khairunnisa (International Journal of Engineering, Science and Information Technology, 2022)
Currently, hoax news is easily spread on social media in seconds. Various kinds of Social Media that exist in cyberspace today, namely Facebook, Instagram, Line, Whatsaap, Telegram, Mechat, Hago, and others, can make it very easy for us to access news or get information compared to us getting information from print media such as newspapers, magazines, Tabloids and so on. The impact on society is very harmful, even severe. Hoax thrives on Social Media, sometimes, we can't prevent it. Fighting deceptions is part of the effort to provide education during the current Covid-19 outbreak. The younger generation can carry out simple socialization through education about hoaxes and start from the surrounding environment, namely family, colleagues, and neighbors. Especially now that almost all people in Indonesia use social media in the form of Whatsapp to facilitate the spread of hoax news. The hoax phenomenon is no longer a strange thing in Indonesia. The danger of hoax news makes people restless and anxious because the information received is not known for its truth or accuracy. Due to the rapid growth of communication technology, it can make hoaxes circulate quickly in seconds in the community through social media.